Enhancement of the Properties of Solar Cells Fabricated by Cadmium Oxide Deposited on Porous Silicon - Mahdi, Raghad R.; Maki, Samier A.; Salihi, Hind A. AL; Abood, Marwa K.; Halbos , Raghad J.; Hassan, Ruqia Abdulhussien; Fayad, M. A. (Peneliti Teknologi Teknik Indonesia, 2024)
This work describes the synthesis of cadmium oxide by a straightforward chemical process and its deposition onto a porous silicon substrate using the drop-casting technique. X-ray diffraction was utilized to determine the structure of the produced cadmium oxide (CdO). The results indicated that the CdO synthesized at room temperature is a cubic polycrystalline structure with a peak at 111. The grain size of the CdO exhibits a high level of homogeneity. The mean roughness of the produced CdO thin film was demonstrated using atomic force microscopy (AFM). The study utilized the optical properties of CdO, revealing its strong absorption and low transmission characteristics. A solar cell was created by depositing cadmium oxide onto prepared porous silicon to verify its high conversion efficiency of approximately 5.8%. The study examines the physical characteristics and effectiveness of a solar cell constructed using cadmium oxide placed on porous silicon.